2021
DOI: 10.1111/1750-3841.15680
|View full text |Cite
|
Sign up to set email alerts
|

Viscozyme L hydrolysis and Lactobacillus fermentation increase the phenolic compound content and antioxidant properties of aqueous solutions of quinoa pretreated by steaming with α‐amylase

Abstract: In this work, red quinoa was successively subjected to α‐amylase steaming, complex enzyme Viscozyme (R) L hydrolysis, and lactic acid bacteria (LAB) fermentation. The total phenolic compound content (TPC), flavonoid content (TFC), and antioxidant capacities of the solvent‐extractable (free) and bound fractions and the individual phenolic compounds released were determined. Compared to steaming with α‐amylase, enzymatic hydrolysis and fermentation of quinoa resulted in approximately 82.6, 26.9, 36.3, and 45.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The extraction of phenolic compounds was performed according to the method described by Zhang et al [ 17 ] with some modifications. O-Lp, O-La, O-Lc, O-Lb, and O-St samples (4 mL) with different fermentation time were collected, mixed with 20 mL of 80% ethanol, and placed in an ultrasonic cleaner (KQ-50E, Kun Shan Ultrasonic Instruments Co., Ltd., Kun Shan, China) at 25 °C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of phenolic compounds was performed according to the method described by Zhang et al [ 17 ] with some modifications. O-Lp, O-La, O-Lc, O-Lb, and O-St samples (4 mL) with different fermentation time were collected, mixed with 20 mL of 80% ethanol, and placed in an ultrasonic cleaner (KQ-50E, Kun Shan Ultrasonic Instruments Co., Ltd., Kun Shan, China) at 25 °C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…casei, Lc. paracasei Flavonoid glycosidase - a) ; Quercetin, kaempferol; ( Zhang et al, 2021 ) Vegetables and leafy/plant substrates Kale Lc. paracasei Flavonoid glycosidase Kaempferol-3- O -sophoroside; kaempferol; ( Shimojo et al, 2018 ) Curly kale juice Lp.…”
Section: Transformation Of Phenolic Compounds In Food Fermentationsmentioning
confidence: 99%
“…Xin et al ( 44 ) studied the wood flour degradation ability of T. fuciformis and its associated cellulase and found that they had a strong synergistic effect, and the degradation ability was significantly improved by 5-fold. Interestingly, Zhang et al ( 45 ) found that the total phenolic content obtained from the co-fermentation of compound enzymes and lactic acid bacteria was much higher than that obtained by single enzyme decomposition. These results were similar to this study, that is, the total phenolic content of EH-AT obtained by enzymatic pre-treatment was higher than that of AE-AT, and the total phenolic content of TF-AT obtained by the combined action of enzymatic hydrolysis and T. fuciformis was much higher than that of AE-AT, showing a strong ability to enrich biological activity.…”
Section: Resultsmentioning
confidence: 99%